Cu(I)-promoted one-pot `SNAr-click reaction' of fluoronitrobenzenes - Durugkar, Kulbhushan A.; Gonnade, Rajesh G.; Ramana, C. V. (Tetrahedron, 2009)
A one-pot two-step sequence involving a nucleophilic aromatic substitution (SNAF) of activated fluorobenzenes with azide nucleophile and in situ Huisgen cycloaddition of the resulting aryl azides with alkynes has been developed for a rapid access to 1,4-substituted triazoles. Control experiments revealed that both the steps are catalyzed by Cu(I) and also the course of reaction as SNAr followed by [3+2]-cycloaddition. (C) 2009 Elsevier Ltd. All rights reserved.